TOXIC POSITIVITY DI KALANGAN MAHASISWA: ANALISIS NARASI DALAM PERSPEKTIF PENDIDIKAN ISLAM PADA MAHASISWA FAI UM BUTON ANGKATAN 2023 - Sitti Nur Hasana; Madi; Abdul Rahim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The growth of social media has shaped the emotional construction and happiness standards of younger generations, including university students. In academic settings, narratives centered on positive thinking, patience (sabar), and surrender to God (tawakkal) are frequently offered as responses to psychological pressure. However, an excessive interpretation of these narratives risks giving rise to the phenomenon of toxic positivity the tendency to impose a positive outlook to the point of dismissing the validity of negative emotions. This study aims to: (1) analyze the dominant forms of toxic positivity narratives among FAI Class of 2023 students; (2) examine their educational impact; and (3) formulate a response from the perspective of Islamic Education. The study employs a qualitative case study approach, utilizing in-depth interviews with purposively selected participants. Data were analyzed thematically and reflectively to identify emerging patterns of meaning. The findings reveal that toxic positivity manifests through religious language particularly sabar and tawakkal interpreted in performative and overly simplistic ways. The value of sabar is reduced to emotional suppression, tawakkal is understood as passive resignation, and academic communication tends to lack emotional validation. The Islamic Education perspective affirms that emotional regulation does not mean the denial of feelings, but rather their proportional and reflective management. Accordingly, a reinterpretation of sabar, a reaffirmation of tawakkal as the integration of personal effort (ikhtiar) and surrender to God, and the cultivation of an empathetic culture within academic environments are all urgently needed. This study contributes to the broader field of Islamic education by integrating spiritual and psychological dimensions in a balanced manner.